Are they listening? : the response of teens to HIV/AIDS prevention messages and campaigns (UNICEF. Office for Barbados and the Eastern Caribbean Christ ChurchBB, 2009)
Seeks to discover the effectiveness of HIV prevention campaigns. Seeks also to find out how such campaigns could be made more effective at reaching teens and bringing about the required behaviour modification to lead to HIV and AIDS prevention.
Keywords: HIV